Sleep-disordered breathing is associated with higher carboxymethyllysine level in elderly women but not elderly men in the cardiovascular health study. (19th May 2017) - Ahiawodzi, Peter D.; Kerber, Richard A.; Taylor, Kira C.; Groves, Frank D.; O'Brien, Elizabeth; Ix, Joachim H.; Kizer, Jorge R.; Djoussé, Luc; Tracy, Russell P.; Newman, Anne B.; Siscovick, David S.; Robbins, John; et al.
Abstract: Context: Carboxymethyl-lysine (CML) results from oxidative stress and has been linked to cardiovascular disease. Objective: The objective of this study is to investigate the association between sleep-disordered breathing (SDB) – a source of oxidative stress – and CML. Materials and methods: About 1002 participants in the Cardiovascular Health Study (CHS) were studied. Results: Women with SDB had significantly higher CML concentration compared with those without SDB (OR = 1.63, 95%CI = 1.03–2.58, p  = 0.04). The association was not significant among men. Discussion: SDB was associated with CML concentration among elderly women but not men in the Cardiovascular Health Study. Conclusion: Accumulation of CML may be an adverse health consequence of SDB